2017
DOI: 10.1016/s1875-5372(17)30185-6
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Wear Resistance of Laser Cladded Ni-based Coatings with Nanometer La 2 O 3 Addition

Abstract: Ni-based coatings with nano-sized feedstock rare earth element (RE, La2O3) addition were produced by laser cladding. Bed of high energy ball milling mixed Ni60A and La2O3 powders were pre-placed onto the substrate 30CrMnSiNi2A before laser cladding. Results show that La segregates in inter dendrite and thus secondary dendrites growth and ripening are limited. The microstructure is refined. Top surface of the cladded coatings displays better refined microstructure which is caused by high La concentration, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The cross sections also present different morphologies, and some obvious porosity can be observed in each case. During the laser cladding process, the CO and CO2 gases are generated by the reaction of WC and CeO2 [20], as shown in Equation (1). Figure 3 shows the cross-sectional morphology of five single coatings with different CeO 2 contents under identical processing parameters.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The cross sections also present different morphologies, and some obvious porosity can be observed in each case. During the laser cladding process, the CO and CO2 gases are generated by the reaction of WC and CeO2 [20], as shown in Equation (1). Figure 3 shows the cross-sectional morphology of five single coatings with different CeO 2 contents under identical processing parameters.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The inorganic oxides of Ln have been used to mitigate galvanic corrosion either by incorporating them into the metallic materials or by making different types of electrodes. Moreover, these oxides strongly impact mechanical properties, as the wear resistance of 30CrMnSiNi2A steel increased 4 times by adding the Ln-based oxides into laser cladding nickel-based coatings . Thus, La-based coatings are considered the best alternative for chromate coatings, providing corrosion resistance and toxicity levels at a minimal scale. ,, Although La is not directly involved in the biological activities of the human body, it is somehow associated with some bacteria as an essential component.…”
Section: Applications and Prospects Of Ln Elementsmentioning
confidence: 99%
“…The study by Liang et al [24] on the Ni-based alloy coating modified with rare earth showed that there were no cracks and pores in the coatings contained 4 %CeO2, 5 % Y2O3, and 5 % La2O3 respectively, and the microstructure was refined, but the study did not mention the effect on properties. Zhao et al [25] reported that the microstructure of Ni-based coating with nanometer La2O3 addition was refined because of La segregates in inter dendrite and thus limiting secondary dendrites growth and ripening, the hardness and wear resistance of the coating were improved in comparison with the base steel.…”
Section: Introductionmentioning
confidence: 99%